The Cycad Genus Cycas May Have Diversified From Indochina and Occupied Its Current Ranges Through Vicariance and Dispersal Events - Mankga, Ledile T.; Yessoufou, Kowiyou; Mugwena, Thendo; Chitakira, Munyaradzi (Frontiers in Ecology and Evolution, 2020)
Biogeographically, cycads were once widely distributed but the extant cycads are restricted to tropical and subtropical regions. They originated ~ 300 Ma and re-diversified recently around 12 Ma, with the genus Cycas being the most rapidly diversified and largely distributed lineage. However, the forces that shaped the diversification and biogeography of the genus remain to be fully understood. Here, we first retrieved and used DNA sequences from GenBank (nuclear: PHYP, RPB1, HZP, AC3, F3H, SAMS and GTP; chloroplasts: plant barcode trnH-psbA, trnL-trnF, trnS-trnG and psbM-trnD) to assemble a complete dated phylogeny of Cycas. Then, we employed the Bayesian Binary Method to reconstruct the historical biogeography of the extant Cycas and finally, using the Bayesian approach for diversification analysis, we explored the evolutionary events that might have shaped the rapid diversification and large distribution of Cycas across the Pacific Islands. Our analysis pointed to Indo-China as the origin of the genus, which may have dispersed firstly across the Pacific Islands during the late Miocene aided by multiple excursions of sea levels and the development of a key innovation, i.e. a spongy endocarp particularly in the seeds of the subsection Rumphiae. The colonization of South China, which was thought to be the origin of the genus, may have occurred more recently aided by both dispersal and vicariance events. However, no significant shifts in the evolutionary events (speciation, extinction, mass extinction) that shaped the diversity of the genus were observed. Overall, our study re-clarifies the historical biogeography and the evolutionary forces that shaped the current diversity of the genus Cycas.